Multiscale occupancy of the Lesser Prairie-Chicken: the role of private lands in conservation of an imperiled bird - Christian A. Hagen (Resilience Alliance, 2020)
Grasslands are one of the most imperiled ecosystems globally, and the Lesser Prairie-Chicken (Tympanuchus pallidicinctus) is an iconic grassland-obligate species with high conservation priority in the USA. Lesser Prairie-Chicken conservation is compounded by its requirement for a spatial hierarchy of heterogeneous habitats, coupled with nearly all (> 95%) of its range being privately owned. The U.S. Department of Agriculture currently offers technical and financial resources that facilitate prairie restoration, e.g., Conservation Reserve Program (CRP), and improve habitat quality and ecosystem services, e.g., Environmental Quality Improvement Program, on private lands. We modeled Lesser Prairie-Chicken occupancy at two scales relative to covariates that described landscape composition and configuration, anthropogenic development, drought-related climatic conditions, and conservation efforts from 2012 to 2016. Large-scale (225 km²) occupancy was most associated with shrubland, grassland patch size, and CRP range-wide. Patterns of small-scale (56.25 km²) occupancy varied regionally, but key covariates included shrubland, grassland, and CRP landcover. These covariate relationships may be useful for identifying conservation practices at different spatial scales and habitat factors that influence Lesser Prairie-Chicken distributions ecoregionally. Notably, CRP-enrolled lands appear to serve as a surrogate for prairie habitat in some ecoregions, especially in conjunction with larger extant patches of native habitat. Although not as influential as CRP at large scales, every 2.25 km² of prescribed grazing increased the odds of site occupancy by 11%. In addition to supported covariates, we found that for every 0.56 km² of industrial development at small scales and 2.25 km² of woodland cover (10%-canopy) at large scales, odds of occupancy decreased by 22% and 13%, respectively. Our results suggest that increased amounts of native grassland and shrubland, and in particular higher levels of CRP enrollment could expand LEPC distribution by as much as 17% (1418-1744 km²). Moreover, our findings illustrate the potential for federal conservation policies to benefit the distribution of an imperiled species.